The role of the adipokines visfatin and leptin in the pathogenesis of rheumatoid arthritis - Meier, Florian Matthias Peter; Justus Liebig University Giessen (My University, 2013)
Rheumatoid arthritis (RA) is a chronic, inflammatory joint disease, which is mainly characterized by a painful affection of multiple joints. The synovial tissue lining the joint cavity is clearly thickened in inflamed joints and activated synovial fibroblasts (SFs) align in the lining layer closely to the cartilage-bone junction. SFs can adhere to, invade into and degrade the cartilage by producing different matrixmetalloproteinases (MMPs). Visfatin and leptin belong to the group of adipokines, molecules released from adipose tissue. Visfatin has been demonstrated to function as an extracellular cytokine, but also as an intracellular enzyme regulating energy metabolism on the cellular level. Leptin on the other hand is known as a hormone regulating food intake at the level of the central nervous system. Recent studies have shown that both proteins are actively participating in the inflammatory immune response affecting arthritic joints in RA. The aim of this work was to detect both leptin and visfatin in the joints of RA patients and to investigate their influence on joint inflammation. Thus, synovial fluid and synovial tissue of RA patients were analyzed. Responses of SFs to the stimulatory effect of visfatin and leptin as well as effects of possible alterations in the cytokine microenvironment on fibroblasts and lymphocytes were studied. Leptin and visfatin are present in the synovial fluid of RA patients, whereas only visfatin was positively correlated to parameters of inflammation such as C-reactive protein (CRP). Visfatin was detectable in the synovial tissue around interstitial vessels, lymphoid aggregates and in the lining layer by immunohistochemistry. A clear change in the gene expression pattern of RASFs was induced by visfatin showing an upregulation of proinflammatory cytokines and MMPs. The most distinct change was seen for the subgroup of chemokines. Stimulation of RASFs with visfatin led to an alteration of the cytokine environment, which was chemoattractive not only for RASFs in an autocrine fashion but also for lymphocytes. Visfatin-conditioned medium increased directed fibroblast migration towards a gradient as well as undirected cell migration and therefore overall cell motility. These and other previously published results lead to the hypothesis that visfatin acts as a proinflammatory cytokine in arthritic joints by enhancing the joint-destructive potential of RASFs and by promoting their accumulation in the lining layer . In contrast, leptin did not significantly influence the gene expression profile of RASFs, neither on the RNA nor the protein levels. Therefore, leptin appears not to be a main trigger of RASF activation. Of note, results from animal models of RA showed that inhibition of the enzymatic activity of visfatin led to an amelioration of the disease. Taken together, the results of this study suggest that visfatin is an important proinflammatory cytokine, which could be a novel therapeutic target in RA.

Die rheumatoide Arthritis (RA) ist eine primär chronisch entzündliche Gelenkerkrankung, die hauptsächlich durch eine schmerzhafte Beteiligung mehrerer Gelenke charakterisiert ist. In einem entzündeten Gelenk zeigt sich die Synovialis deutlich verdickt und es finden sich aktivierte synoviale Fibroblasten (SF), die sich in einem sogenannten lining layer am Knorpel-Knochenübergang sammeln. Sie adhärieren aktiv am Gelenkknorpel, wandern in ihn ein und zerstören ihn, unter anderem durch die Produktion verschiedener Matrixmetalloproteinasen (MMP). Visfatin und Leptin sind Zytokine aus dem Fettgewebe und werden dementsprechend als Adipozytokine bezeichnet. Visfatin zeigt neben der Funktion eines extrazellulären Zytokins auch intrazelluläre enzymatische Aktivität im Energiehaushalt der Zellen. Leptin ist bekannt als Hormon, das zentral das Hungergefühl hemmt. Für beide konnte kürzlich gezeigt werden, dass sie aktiv an der entzündlichen Immunantwort in rheumatischen Gelenken beteiligt sind. Ziel dieser Arbeit war es herauszufinden, ob sowohl Visfatin als auch Leptin im Gelenk von RA Patienten vorkommen und ob sie einen Einfluss auf die Entzündung im Gelenk nehmen. Hierzu wurden die Synovialflüssigkeit und die Synovialis von RA Patienten analysiert, die Antwort synovialer Fibroblasten auf die Stimulation mit Visfatin und Leptin untersucht und festgestellt, ob sich durch diese Einflussnahme das Zytokinmilieu verändert und welcher Einfluss dabei auf die SF und Lymphozyten entsteht. Es konnte gezeigt werden, dass beide Visfatin und Leptin in der Synovialflüssigkeit von RA Patienten vorliegen, wobei sich nur für Visfatin eine Korrelation zu Entzündungsparametern, wie dem C-reaktiven Peptid, zeigte. Im Synovialgewebe konnte nur Visfatin und hier nur im lining layer , in Endothelien und Lymphaggregaten gefunden werden. Visfatin hatte einen deutlichen Einfluss auf die Genexpression von RASF, indem proinflammatorische Zytokine und MMP induziert wurden. Am deutlichsten jedoch wurden Chemokine reguliert. Die Stimulation von RASF mit Visfatin führte zu einem veränderten Zytokinmilieu, das chemoattraktiv für RASF selbst, aber auch für Lymphozyten war. Es konnte gezeigt werden, dass das durch Visfatin konditionierte Medium sowohl die gerichtete Migration von Fibroblasten als auch die ungerichtete Migration und somit sie generelle Beweglichkeit der SF verstärkt. Diese Beobachtungen führen neben anderen bereits bekannten zu der Annahme, dass Visfatin als proinflammatorisches Zytokin im entzündeten Gelenk fungiert, indem es die gelenkzerstörende Antwort der RASF verstärkt und zu deren vermehrten Anordnung im lining layer beiträgt. Leptin zeigte im Vergleich zu Visfatin keine wesentliche Beeinflussung der RASF, weder auf die Genexpression noch auf die Proteinproduktion proinflammatorischer Zytokine. In Tiermodellen der RA konnte bereits gezeigt werden, dass die Inhibition der enzymatischen Aktivität des Visfatins zu einer deutlichen Besserung des Verlaufs führt. Die Ergebnisse dieser Studie untermauern, dass Visfatin ein neues entzündungsförderndes Zytokin und die Blockade der enzymatischen Aktivität ein mögliches, neuartiges Therapiekonzept in der RA ist.
Die Rolle der Adipozytokine Visfatin und Leptin in der Pathogenese der rheumatoiden Arthritis
Keywords: ddc:610